![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, ( x - 3 ) . ( x - 4 ) = 0
=> x - 3 = 0 hoặc x - 4 = 0
Nếu x - 3 = 0 => x = 3
Nếu x - 4 = 0 => x = 4
b, (\(\frac{1}{2}\)x - 4 ) . ( x - \(\frac{1}{4}\)) = 0
=>( \(\frac{1}{2}\)x - 4 ) = 0 Hoặc ( x - \(\frac{1}{4}\)) = 0
Nếu ( \(\frac{1}{2}\)x - 4 ) = 0 => x = \(\frac{8}{1}\)
Nếu ( x - \(\frac{1}{4}\)) = 0 => x = \(\frac{1}{4}\)
c, (\(\frac{1}{3}\)- x ) . ( \(\frac{1}{2}\)+ 1 : x ) = 0
=> ( \(\frac{1}{3}\)- x ) = 0 Hoặc ( \(\frac{1}{2}\)+ 1 : x ) = 0
Nếu (\(\frac{1}{3}\)- x ) = 0 => x = \(\frac{1}{3}\)
Nếu ( \(\frac{1}{2}\)+ 1 : x ) = 0 => x = \(\frac{-2}{1}\)
d, ( x + 3 ) . ( x - 4 ) + 2.(x + 3 ) = 0
=> (X + 3 ) = 0 Hoặc ( x - 4 ) = 0 Hoặc 2. ( x + 3 ) = 0
Nếu x + 3 = 0 => x = 0
Nếu ( x - 4 ) = 0 => x = 4
Nếu 2.(x + 3) = 0 => x = 3
# Cụ MAIZ
a. ( x - 3 ) ( x - 4 ) = 0
<=> \(\orbr{\begin{cases}x-3=0\\x-4=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=3\\x=4\end{cases}}\)
b. \(\left(\frac{1}{2}x-4\right)\left(x-\frac{1}{4}\right)=0\)
<=> \(\orbr{\begin{cases}\frac{1}{2}x-4=0\\x-\frac{1}{4}=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=8\\x=\frac{1}{4}\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài làm :
\(a\text{)}...\Leftrightarrow\orbr{\begin{cases}x-3=0\\x-4=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=4\end{cases}}\)
\(b\text{)}...\Leftrightarrow\orbr{\begin{cases}\frac{1}{2}x-4=0\\x-\frac{1}{4}=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}\frac{1}{2}x=4\\x=0+\frac{1}{4}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=8\\x=\frac{1}{4}\end{cases}}\)
\(c\text{)}...\Leftrightarrow\orbr{\begin{cases}\frac{1}{3}-x=0\\\frac{1}{2}+1\div x=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{3}-0\\1\div x=-\frac{1}{2}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=-2\end{cases}}\)
\(d\text{)}...\Leftrightarrow\left(x+3\right)\left(x-4+2\right)=0\Leftrightarrow\left(x+3\right)\left(x-2\right)=0\Leftrightarrow\orbr{\begin{cases}x+3=0\\x-2=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-3\\x=2\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài làm :
\(a,\left(x-3\right)\left(x-4\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-3=0\\x-4=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=4\end{cases}}\)
\(b,\left(\frac{1}{2}x-4\right)\left(x-\frac{1}{4}\right)=0\)
\(\Rightarrow\orbr{\begin{cases}\frac{1}{2}x-4=0\\x-\frac{1}{4}=0\end{cases}}\Rightarrow\orbr{\begin{cases}\frac{1}{2}x=4\\x=\frac{1}{4}\end{cases}}\Rightarrow\orbr{\begin{cases}x=8\\x=\frac{1}{4}\end{cases}}\)
\(c,\left(\frac{1}{3}-x\right).\left(\frac{1}{2}+1:x\right)=0\)
\(\Rightarrow\orbr{\begin{cases}\frac{1}{3}-x=0\\\frac{1}{2}+1:x=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=-2\end{cases}}\)
\(d,\left(x+3\right)\left(x-4\right)+2\left(x+3\right)=0\)
\(\Rightarrow\left(x+3\right)\left(x-4+2\right)=0\)
\(\Rightarrow\left(x+3\right)\left(x-2\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+3=0\\x-2=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-3\\x=2\end{cases}}\)
Học tốt nhé
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài làm :
\(a\text{)}...\Leftrightarrow\orbr{\begin{cases}x-3=0\\x-4=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=4\end{cases}}\)
\(b\text{)}...\Leftrightarrow\orbr{\begin{cases}\frac{1}{2}x-4=0\\x-\frac{1}{4}=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}\frac{1}{2}x=4\\x=0+\frac{1}{4}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=8\\x=\frac{1}{4}\end{cases}}\)
\(c\text{)}...\Leftrightarrow\orbr{\begin{cases}\frac{1}{3}-x=0\\\frac{1}{2}+1\div x=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{3}-0\\1\div x=-\frac{1}{2}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=-2\end{cases}}\)
\(d\text{)}...\Leftrightarrow\left(x+3\right)\left(x-4+2\right)=0\Leftrightarrow\left(x+3\right)\left(x-2\right)=0\Leftrightarrow\orbr{\begin{cases}x+3=0\\x-2=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-3\\x=2\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left|\sqrt{2}-x\right|=\sqrt{2}\)
\(\Rightarrow\orbr{\begin{cases}\sqrt{2}-x=\sqrt{2}\\\sqrt{2}-x=-\sqrt{2}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=2\sqrt{2}\end{cases}}}\)
b) \(\left|x+1\right|=\sqrt{3}+2\)
\(\Rightarrow\orbr{\begin{cases}x+1=\sqrt{3}+2\\x+1=-\sqrt{3}-2\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\sqrt{3}+1\\x=-\sqrt{3}-3\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x + 2)2 = 81
=> (x + 2)2 = 92
=> \(\orbr{\begin{cases}x+2=-9\\x+2=9\end{cases}}\Rightarrow\orbr{\begin{cases}x=-11\\x=7\end{cases}}\)
b) 5x + 5x + 2 = 650
=> 5x + 5x . 52 = 650
=> 5x + 5x . 25 = 650
=> 5x (25 + 1) = 650
=> 5x . 26 = 650
=> 5x = 650 : 26
=> 5x = 25
=> 5x = 52
=> x = 2
d) (2x - 1)2 - 5 = 20
=> (2x - 1)2 = 25
=> (2x - 1)2 = 52
=> \(\orbr{\begin{cases}2x-1=5\\2x-1=-5\end{cases}\Rightarrow\orbr{\begin{cases}2x=6\\2x=-4\end{cases}\Rightarrow}\orbr{\begin{cases}x=3\\x=-2\end{cases}}}\)
g) (x - 1)3 = (x - 1)
=> (x - 1)3 - (x - 1) = 0
=> (x - 1) .[(x - 1)2 - 1] = 0
=> \(\orbr{\begin{cases}x-1=0\\\left(x-1\right)^2-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=1\\\left(x-1\right)^2=1^2\end{cases}\Rightarrow}\orbr{\begin{cases}x=1\\x-1=\pm1\end{cases}}}\)
Nếu x - 1 = 1
=> x = 2
Nếu x - 1 = -1
=> x = 0
Vậy \(x\in\left\{0;1;2\right\}\)
a) \(\left|x-2\right|=3\)
\(\Rightarrow\orbr{\begin{cases}x-2=3\\x-2=-3\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=3+2=5\\x=-3+2=-1\end{cases}}\)
Vậy x=5 hoặc x=-1
Ta có :\(\left|x-2\right|=3\)
\(=>\orbr{\begin{cases}x-2=-3\\x-2=3\end{cases}}\)
\(=>\orbr{\begin{cases}x=-1\\x=5\end{cases}}\)